Evolution and perspectives of the bioenergy applications in Spain - Paredes-Sánchez, José P.; López-Ochoa, Luis M.; López-González, Luis M.; Las-Heras-Casas, Jesús; Xiberta-Bernat, Jorge (Journal of cleaner production, 2019)
To mitigate the effects of global warming, the European Union must reduce its dependence on foreign fossil fuels to produce energy. Biomass from forests and agroforestry residues are a readily available source of domestic renewable energy. However, further technological developments must be made in order to foster its use in machines and thermal engines. The present study analyses the current situation of biomass energy in Spain as well as its future prospects, potential challenges and opportunities moving forward. This analysis is performed through a review based on bioenergy resources, technology and management to provide recommendations and carry out a more comprehensive energy assessment. Non-food biomass resources are intended to be useful in the development of bioenergy industrial sector. This study is applied to Spain due to its remarkable forests and wealth of agricultural areas. The methodology is based on three phases of energy conversion: resources, technology and management. The main achievements are pathways definition from resource to bioenergy application in Spain. Bioenergy advances offer management drive forces to meeting the energy and environmental challenges in the European Union. •Biofuels could profitably replace conventional fuels by bioeconomy.•New energy conversion strategies can further develop the bioenergy sector.•European countries must pay attention to technical solutions for energy production.•Circular biomass conversion has great potential available in Spain.